Processing method of hard alloy bar for PCB milling cutter

Through the ratio of WC, CoCrFeMnNi, Cr3C2, cBN powders and the ball milling and four-stage sintering processes of CNTs/Ni solvents, the problem of insufficient toughness and wear resistance of PCB milling cutter materials is solved, and the overall performance of cemented carbide rods is improved and Service life.

CN119162483APending Publication Date: 2024-12-20HEYUAN FUMA CEMENTED CARBIDE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310016.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing PCB milling cutter materials are insufficient toughness and poor wear resistance in high-speed and high-load processing environments, resulting in limited service life and processing efficiency.

Method used

The ratio of WC powder, CoCrFeMnNi powder, Cr3C2 powder and cBN powder is used for ball milling, and CNTs/Ni solvent is added, and high-performance cemented carbide rods are formed through molding and four-stage sintering process.

Benefits of technology

It improves the wear resistance, thermal stability and corrosion resistance of cemented carbide rods, enhances mechanical properties and service life, improves impact resistance and magnetic properties, and adapts to high-stress and high-wear environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050374150000121
    Figure BDA0005050374150000121
  • Figure BDA0005050374150000131
    Figure BDA0005050374150000131
Patent Text Reader

Abstract

The invention discloses a processing method of a hard alloy bar for a PCB (Printed Circuit Board) milling cutter, which comprises the following steps of: putting raw materials obtained by proportioning into a ball mill, and adding a CNTs / Ni solvent for ball milling to form ball-milled slurry; the WC-CoCrFeMnNi is subjected to compression molding, and a hard alloy bar blank is obtained; the degreased and dried hard alloy bar blank is put into a sintering furnace to be sintered; the CrC and cBN double-grain inhibitor is adopted, the abrasion resistance, the heat stability and the corrosion resistance of the hard alloy bar are improved, the CNTs / Ni solvent can enhance the heat conductivity and the coercive force of the material, and then the compactness and the impact resistance of the material are improved; and a four-stage sintering process is adopted in the sintering process, so that the compactness and the grain uniformity of the material can be improved, and a structure in which an FCC phase and a BCC phase are combined is formed, and the prepared material has high strength, high toughness and crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cemented carbide, and in particular to a processing method of a cemented carbide rod for a PCB milling cutter. Background Art

[0002] Due to its excellent hardness, wear resistance and corrosion resistance, cemented carbide materials are widely used in the manufacture of various cutting tools, molds and wear-resistant parts, especially in the field of electronic manufacturing. With the continuous advancement of PCB printed circuit board processing technology, higher requirements are placed on milling cutter materials. Modern PCB milling cutters need to maintain high precision and long life in high-speed and high-load processing environments. Therefore, the performance requirements for PCB milling cutter materials have become particularly stringent.

[0003] In the prior art, conventional cemented carbide rods usually use WC as a matrix and Co as a binder for compression molding and sintering. However, with the increasing application of multi-layer PCB boards, these technical changes have made the processing of PCB milling cutters more and more difficult, resulting in PCB milling cutters gradually exposing problems such as insufficient toughness, poor wear resistance, and performance degradation in high temperature and high stress environments, thereby restricting the service life and processing efficiency of PCB milling cutters.

[0004] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for processing a cemented carbide rod for a PCB milling cutter, which can improve the toughness, wear resistance and hardness of the PCB milling cutter.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A method for processing a cemented carbide rod for a PCB milling cutter comprises the following steps:

[0008] S1. Prepare the raw materials according to the following weight percentages: WC powder: 80-92wt%, CoCrFeMnNi powder: 4-12wt%, Cr 3 C 2 Powder: 0.5-1.4wt%, cBN powder: 2-8wt%;

[0009] S2, putting the raw materials obtained in step S1 into a ball mill, with a ball-to-material ratio of 3-4:1, a ball milling speed of 400-600 r / min, and a ball milling time of 22-36 h, and then adding CNTs / Ni solvent for ball milling for 2-4 h to form a uniform ball milling slurry;

[0010] Wherein, the weight percentage of the CNTs / Ni solvent in the mixed slurry is 1-4wt%;

[0011] S3, drying the ball-milled slurry obtained in step S2 in a vacuum drying oven, and obtaining WC-CoCrFeMnNi composite powder after sieving and granulating;

[0012] S4, pouring the WC-CoCrFeMnNi composite powder into a cylindrical graphite mold, and compression molding the WC-CoCrFeMnNi composite powder by a hydraulic press to obtain a cemented carbide rod blank;

[0013] S5, performing solvent degreasing treatment on the cemented carbide rod blank in deionized water, the degreasing time is 5-7h, the degreasing temperature is 45-65°C, and vacuum drying is performed after degreasing;

[0014] S6. Put the degreased and dried cemented carbide rod blank into a sintering furnace for sintering, cool it down after taking it out of the furnace, and grind and polish it to obtain a cemented carbide rod.

[0015] Using the above technical scheme, the preparation method of the CNTs / Ni solvent is as follows: nickel sulfate, potassium sodium tartrate, sodium citrate, and anhydrous sodium carbonate are added to a mixed solution of deionized water and hydrazine hydrate, and the mixture is stirred evenly to obtain a chemical plating solution, and then CNTs particles are added to the chemical plating solution, and sodium hydroxide is added dropwise to maintain the pH value at 8 to 9. After stirring in a 65-75°C water bath for 1-2 hours, the mixture is centrifuged to neutrality, and dried to obtain CNTs / Ni particles. Finally, the CNTs / Ni particles are placed in an ethanol solution for ultrasonic dispersion for 20-30 minutes to obtain a CNTs / Ni solvent.

[0016] By adopting the above-mentioned technical solutions, in the chemical plating solution, the weight ratio of deionized water to hydrazine hydrate is 50:1, the content of nickel sulfate is 0.13-0.15 g / L, the content of potassium sodium tartrate is 0.07-0.09 g / L, the content of sodium citrate is 0.1-0.12 g / L, and the content of anhydrous sodium carbonate is 0.1-0.12 g / L.

[0017] Using the above technical solutions, the weight ratio of CNTs particles to chemical plating solution is 2:10.

[0018] Using the above technical solutions, the weight ratio of CNTs / Ni particles to ethanol solution is 2:20.

[0019] By adopting the above technical solutions, in step S2, the diameter of the ball mill in the ball mill is 4-12 mm, and the ball mill is a zirconia ball.

[0020] By adopting the above technical solutions, in step S1, the particle size of the WC powder is 0.4-1 μm, the particle size of the CoCrFeMnNi powder is 0.6-1.2 μm, and the particle size of the Cr3 C 2 The particle size of the powder is 0.2 to 0.4 μm, and the particle size of the cBN powder is 0.1 to 0.3 μm.

[0021] By adopting the above-mentioned technical solutions, in step S3, the particle size of the WC-CoCrFeMnNi composite powder is 0.2-0.8 μm.

[0022] By adopting the above-mentioned technical solutions, in step S4, the pressure of the hydraulic press on the cylindrical graphite mold is 150-240 MPa, and the molding time is 4-8 minutes.

[0023] Using the above technical solutions, in step S6, the cemented carbide rod blank is sintered by a four-stage sintering method;

[0024] S61, first stage: after evacuating the sintering furnace, supply hydrogen, and heat the sintering furnace to 420-630°C at a rate of 30-45°C / min and keep it warm for 4-6h;

[0025] S62, second stage: heating the sintering furnace to 1340-1460°C at a rate of 50-65°C / min, supplying argon gas, and sintering in an inert gas environment for 50-75 minutes;

[0026] S63, the third stage: continue to supply argon gas to make the pressure in the sintering furnace reach 55-75mbar, and raise the temperature to 1570-1590℃, and keep it warm for 30-45min;

[0027] S64, the fourth stage: After naturally cooling to 950-1050°C, keep warm for 20-40 minutes, and then cool to room temperature at a rate of 55-70°C / min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts Cr 3 C 2The powder and cBN powder dual grain inhibitor can make the cemented carbide rod obtain higher wear resistance, excellent thermal stability and corrosion resistance, thereby improving the overall mechanical properties and service life; CNTs in CNTs / Ni solvent can form a high thermal conductivity channel during the sintering process, thereby improving the heat distribution and making the sintered body denser. At the same time, CNTs can connect the WC interface, reduce thermal resistance, and increase the thermal diffusion coefficient of the cemented carbide rod; Ni particles on the surface of CNTs / Ni can be magnetized to increase the coercive force of the cemented carbide rod, thereby enhancing resistance to external magnetic fields, so that the PCB milling cutter has better impact resistance during high-load and high-speed cutting; during the sintering process In the process, a four-stage sintering method is adopted. In the first stage, the oxides are reduced by hydrogen to ensure the purity of the material and improve the density and strength of the material. The rapid heating and inert gas protection in the second stage can effectively prevent excessive grain growth and oxidation, ensure the densification and uniformity of the material, and improve the mechanical properties. The high temperature insulation in the third stage can promote the full development of the FCC phase, make the grain structure uniform and stable, and enhance the toughness and plasticity of the material. The cooling in the fourth stage controls the transformation of the FCC phase to the BCC phase, forming a reasonable ratio of the FCC phase and the BCC phase, so that the material has both high toughness and high strength, adapts to high stress and high wear environment, and improves the crack resistance. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0031] The present invention provides a method for processing a cemented carbide rod for a PCB milling cutter.

[0032] The following steps are involved:

[0033] S1. Prepare the raw materials according to the following weight percentages: WC powder: 80-92wt%, CoCrFeMnNi powder: 4-12wt%, Cr 3 C 2Powder: 0.5-1.4wt%, cBN powder: 2-8wt%; WC is the main component of cemented carbide, with extremely high hardness and wear resistance, so that it can maintain a sharp edge during cutting and grinding, and has good wear resistance; CoCrFeMnNi, as a high entropy alloy, has excellent toughness, corrosion resistance and high temperature stability. In cemented carbide, as a binder, it can improve the toughness and fracture resistance of cemented carbide; Cr 3 C 2 It is a grain inhibitor that can effectively inhibit the growth of WC grains during cemented carbide sintering, thereby maintaining a fine and uniform microstructure and improving the hardness and toughness of cemented carbide materials. 3 C 2 It can also enhance the oxidation resistance and corrosion resistance of cemented carbide materials; cBN has extremely high hardness, wear resistance and thermal stability. The addition of cBN can significantly improve the hardness, wear resistance and thermal cracking resistance of cemented carbide, while maintaining good structural stability under high temperature conditions.

[0034] S2, put the raw materials obtained in step S1 into a ball mill, the ball-to-material ratio is 3-4:1, the ball milling speed is 400-600r / min, the ball milling time is 22-36h, and then add CNTs / Ni solvent for ball milling for 2-4h to form a uniform ball milling slurry; ball milling the raw materials can refine the powder particles, thereby improving the densification effect during the sintering process, improving the mechanical properties, and reducing the cracking problem caused by uneven material particle size; CNTs in CNTs / Ni solvent can form a high thermal conductivity channel during the sintering process, improve heat distribution, and make the sintered body denser. At the same time, CNTs can connect the WC interface, reduce thermal resistance, and increase the thermal diffusion coefficient of the cemented carbide rod. The Ni particles on the surface of CNTs / Ni can be magnetized, which increases the coercive force of the cemented carbide rod, thereby enhancing the resistance to the external magnetic field, so that the PCB milling cutter has better impact resistance during high-load and high-speed cutting.

[0035] Among them, the weight percentage of the CNTs / Ni solvent in the mixed slurry is 1-4wt%; if the CNTs / Ni solvent content is too low, the reinforcement effect will be unclear; if the CNTs / Ni solvent content is too high, it will easily lead to difficulty in dispersion and increase agglomeration, which is not conducive to the material properties of cemented carbide.

[0036] S3, drying the ball-milled slurry obtained in step S2 through a vacuum drying oven, and obtaining WC-CoCrFeMnNi composite powder after screening and granulation; drying through a vacuum drying oven can effectively remove the residual solvent in the ball-milled slurry, prevent unnecessary chemical reactions or gas release during subsequent processing, thereby maintaining the purity of the powder; through screening and granulation, these block materials can be broken up and made into uniform powder particles, thereby improving the fluidity of the powder, so that it can fill the mold more evenly during subsequent compression molding, and avoid structural defects caused by uneven distribution of powder.

[0037] S4. Pour the WC-CoCrFeMnNi composite powder into a cylindrical graphite mold, and compression-mold the WC-CoCrFeMnNi composite powder by a hydraulic press to obtain a cemented carbide rod blank. During the compression molding process, the pressure applied by the hydraulic press can effectively compress the gaps between the WC-CoCrFeMnNi composite powders, thereby increasing the density of the blank and preventing sintering shrinkage in the subsequent sintering process, thereby improving the density and mechanical properties of the sintered body.

[0038] S5. Solvent degreasing treatment is performed on the cemented carbide rod blank in deionized water for 5-7 hours at a degreasing temperature of 45-65°C, followed by vacuum drying. Degreasing treatment can remove residual solvent on the cemented carbide rod blank to prevent adverse chemical reactions or physical defects during sintering. The use of deionized water can keep the surface and interior of the blank pure, thereby improving the purity and mechanical properties of the subsequent sintered body. The degreasing temperature is controlled at 45-65°C. While removing the solvent, it can also avoid cracks or deformation of the blank microstructure caused by excessive temperature.

[0039] S6. Put the degreased and dried cemented carbide rod blank into a sintering furnace for sintering, cool it out of the furnace, and grind and polish it to obtain a cemented carbide rod. High-temperature sintering can cause diffusion and recrystallization between powder particles to eliminate the pores between particles and achieve densification of the blank.

[0040] Furthermore, the preparation method of the CNTs / Ni solvent is: adding nickel sulfate, potassium sodium tartrate, sodium citrate, and anhydrous sodium carbonate to a mixed solution of deionized water and hydrazine hydrate, stirring evenly to obtain a chemical plating solution, then adding CNTs particles to the chemical plating solution, adding sodium hydroxide dropwise to maintain the pH value at 8-9, stirring in a 65-75°C water bath for 1-2 hours, then centrifuging to neutrality, drying to obtain CNTs / Ni particles, and finally placing the CNTs / Ni particles in an ethanol solution for ultrasonic dispersion for 20-30 minutes to obtain a CNTs / Ni solvent. Nickel sulfate can provide nickel ions, potassium sodium tartrate and sodium citrate can act as complexing agents to stabilize nickel ions and prevent them from precipitating prematurely in the solution, anhydrous sodium carbonate can adjust the pH value of the solution to ensure that the reaction is carried out in a suitable alkaline environment, and by stirring evenly, it can be ensured that each component is fully dissolved to form a uniform chemical plating solution, so that nickel ions can be uniformly deposited on the surface of CNTs; since CNTs need to be nickel-plated under appropriate pH conditions, too high or too low pH will affect the quality of the coating, and by adding sodium hydroxide to adjust the pH to 8-9, the stability of the nickel deposition process can be improved to prevent nickel particles from agglomerating; ultrasonic dispersion can disperse the particles to destroy the van der Waals force between the particles through mechanical vibration, so that the particles are evenly distributed in the ethanol solution, and ethanol, as a dispersion medium, is highly volatile and chemically inert, and can be easily removed in subsequent processes without adversely affecting other components.

[0041] Furthermore, in the chemical plating solution, the weight ratio of deionized water to hydrazine hydrate is 50:1, the content of nickel sulfate is 0.13-0.15 g / L, the content of potassium sodium tartrate is 0.07-0.09 g / L, the content of sodium citrate is 0.1-0.12 g / L, and the content of anhydrous sodium carbonate is 0.1-0.12 g / L. Deionized water as a solvent can provide a pure reaction environment to avoid the interference of impurities on the chemical reaction; hydrazine hydrate as a reducing agent can reduce nickel ions to metallic nickel. The weight ratio of deionized water to hydrazine hydrate is set to 50:1, which can ensure that there is enough hydrazine hydrate in the plating solution to reduce nickel ions, and at the same time, hydrazine hydrate is not overused to avoid the occurrence of side reactions.

[0042] Furthermore, the weight ratio of CNTs particles to chemical plating solution is 2:10. If the amount of CNTs is too much, relative to the amount of nickel ions in the plating solution, the nickel layer will not be able to evenly cover all CNTs surfaces, resulting in uneven plating and affecting the performance of the material; and if the amount of CNTs is too little, nickel will be reduced to nickel particles in the solution instead of being deposited on the surface of CNTs, resulting in a waste of resources. In addition, CNTs particles have strong van der Waals forces and are easy to agglomerate. If the proportion of CNTs in the chemical plating solution is too high, the mutual attraction between particles will increase, resulting in serious agglomeration and affecting the uniform deposition of the nickel layer.

[0043] Furthermore, the weight ratio of CNTs / Ni particles to ethanol solution is 2:20. CNTs / Ni particles tend to agglomerate after drying, especially after chemical nickel plating, the nickel layer increases the adhesion between particles, and ethanol as a solvent has low surface tension and excellent dispersibility, which can effectively disperse these agglomerated particles.

[0044] Furthermore, in step S2, the diameter of the ball mill in the ball mill is 4 to 12 mm, and the ball mill is a zirconia ball. Zirconia has extremely high hardness and wear resistance, and can effectively crush cemented carbide materials; at the same time, the zirconia ball will not be easily worn or broken during the ball milling process, thereby increasing the service life of the ball mill.

[0045] Furthermore, in step S1, the particle size of the WC powder is 0.4-1 μm, the particle size of the CoCrFeMnNi powder is 0.6-1.2 μm, and the particle size of the Cr 3 C 2 The particle size of the powder is 0.2-0.4 μm, and the particle size of the cBN powder is 0.1-0.3 μm. These particle distribution and size control can optimize the microstructure during the sintering process and ensure that the components are evenly distributed in the material.

[0046] Furthermore, in step S3, the particle size of the WC-CoCrFeMnNi composite powder is 0.2-0.8 μm. Smaller particles have higher specific surface area and surface energy, which makes the atomic diffusion between particles faster, which is beneficial to the shrinkage and densification of the sintered body.

[0047] Furthermore, in step S4, the pressure of the hydraulic press on the cylindrical graphite mold is 150-240 MPa, and the molding time is 4-8 minutes. The molding process compacts the powder by applying high pressure to reduce the voids in the powder, so that the particles are in closer contact, and form a high-density cemented carbide rod blank.

[0048] Further, in step S6, the cemented carbide rod blank is sintered using a four-stage sintering method;

[0049] S61. The first stage: After the sintering furnace is evacuated, hydrogen is supplied, and the sintering furnace is heated to 420-630℃ at a rate of 30-45℃ / min and then kept warm for 4-6h; in the initial sintering stage, there may be trace oxides in the cemented carbide rod blank due to the pretreatment process. These oxides will affect the density and strength of the material at high temperatures. The introduction of hydrogen can reduce these oxides to metals to avoid the degradation of material properties due to the presence of oxides during the sintering process. Hydrogen can also prevent the reformation of oxides at high temperatures to ensure that the material maintains a high degree of purity; the initial sintering temperature of 420-630℃ can decompose and remove residual organic matter, but the temperature is not too high to avoid unnecessary changes in the material structure during the initial sintering process or cause the sintered body to sinter prematurely. Too high a temperature will cause the cemented carbide rod blank to sinter prematurely, leaving organic matter inside and forming defects or holes.

[0050] S62. The second stage: the sintering furnace is heated to 1340-1460°C at a rate of 50-65°C / min, and then argon is supplied, and sintering is carried out in an inert gas environment for 50-75 minutes; a faster heating rate can quickly heat the material to the sintering temperature, so that the surface of the powder particles quickly reaches a high temperature, reducing the time spent in the intermediate temperature stage, and avoiding excessive grain growth or uneven sintering in a range below the sintering temperature; maintaining the sintering temperature at 1340-1460°C can optimize the diffusion and bonding between the powder particles, so that the material can be highly densified, thereby forming a dense sintered body with high strength and good toughness; during the high-temperature sintering process, some metal elements, such as cobalt, nickel, chromium, etc., are easily oxidized, resulting in a decrease in the performance of the cemented carbide rod. By supplying argon during the sintering process, an inert environment can be formed to avoid the formation of oxides, thereby maintaining the chemical purity of the material and improving the mechanical properties and corrosion resistance of the product.

[0051] S63, the third stage: continue to supply argon gas to make the pressure in the sintering furnace reach 55-75mbar, and heat up to 1570-1590℃, and keep it warm for 30-45min; in the high temperature range of 1570-1590℃, the atoms in the material have sufficient kinetic energy, which promotes the diffusion and rearrangement of atoms, so that a uniform FCC phase grain structure is formed in this temperature range. By keeping warm for 30-45min, the FCC phase can be fully developed, making the grain structure uniform and stable, and then reaching a stable state in the material;

[0052] S64, the fourth stage: After naturally cooling to 950-1050°C, keep warm for 20-40 minutes, and then cool to room temperature at a rate of 55-70°C / min. When the temperature is lowered to 950-1050℃, the atomic arrangement inside the material gradually tends to a lower energy state, which in turn promotes the transformation of part of the FCC phase in the material to the BCC phase. The 20-40min holding time ensures the full phase change process, thereby forming a stable BCC phase structure; then the temperature is lowered to room temperature at a rate of 55-70℃ / min. Rapid cooling inhibits excessive phase change to retain part of the FCC phase, so that the FCC phase and BCC phase in the material are maintained at a reasonable ratio. Since the FCC phase has higher toughness and good plasticity, and the BCC phase has higher strength and hardness, the structure of the combination of the FCC phase and the BCC phase makes the cemented carbide rod have both good toughness and high strength, so as to be suitable for high stress and high wear PCB board processing applications; and when the cemented carbide rod is subjected to external stress, the FCC phase can absorb part of the stress, while the high strength of the BCC phase can resist the concentration of stress. This stress dispersion mechanism can effectively reduce the risk of brittle fracture of the material and improve the crack resistance.

[0053] Example 1

[0054] Embodiment 1 of the present invention provides a method for processing a cemented carbide rod for a PCB milling cutter.

[0055] The following steps are involved:

[0056] S1. Prepare the raw materials according to the following weight percentages: WC powder: 80wt%, CoCrFeMnNi powder: 12wt%, Cr 3 C 2 Powder: 0.5wt%, cBN powder: 7.5wt%; wherein the particle size of the WC powder is 0.4μm, the particle size of the CoCrFeMnNi powder is 0.6μm, and the particle size of the Cr 3 C 2 The particle size of the powder is 0.2 μm, and the particle size of the cBN powder is 0.1 μm;

[0057] S2, putting the raw materials obtained in step S1 into a ball mill, with a ball-to-material ratio of 3:1, a ball milling speed of 400 r / min, and a ball milling time of 36 h, and then adding CNTs / Ni solvent for ball milling for 4 h to form a uniform ball milling slurry; wherein the ball milling body in the ball mill has a diameter of 12 mm and the ball milling body is a zirconia ball;

[0058] The weight percentage of the CNTs / Ni solvent in the mixed slurry is 4wt%; the preparation method of the CNTs / Ni solvent is: adding nickel sulfate, potassium sodium tartrate, sodium citrate, and anhydrous sodium carbonate to a mixed solution of deionized water and hydrazine hydrate, stirring evenly to obtain a chemical plating solution, then adding CNTs particles to the chemical plating solution, dripping sodium hydroxide to maintain the pH value at 9, stirring in a 65°C water bath for 1h, then centrifuging to neutrality, drying to obtain CNTs / Ni particles, and finally placing the CNTs / Ni particles in an ethanol solution for ultrasonic dispersion for 20min to obtain a CNTs / Ni solvent;

[0059] Among them, in the chemical plating solution, the weight ratio of deionized water and hydrazine hydrate is 50:1, the content of nickel sulfate is 0.13 g / L, the content of potassium sodium tartrate is 0.07 g / L, the content of sodium citrate is 0.1 g / L, and the content of anhydrous sodium carbonate is 0.1 g / L; the weight ratio of CNTs particles to chemical plating solution is 2:10; the weight ratio of CNTs / Ni particles to ethanol solution is 2:20.

[0060] S3, drying the ball-milled slurry obtained in step S2 in a vacuum drying oven, and obtaining WC-CoCrFeMnNi composite powder after sieving and granulating, wherein the particle size of the WC-CoCrFeMnNi composite powder is 0.2 μm;

[0061] S4, pouring the WC-CoCrFeMnNi composite powder into a cylindrical graphite mold, and molding the WC-CoCrFeMnNi composite powder by a hydraulic press to obtain a cemented carbide rod blank; wherein the pressure of the hydraulic press on the cylindrical graphite mold is 240 MPa, and the molding time is 4 minutes;

[0062] S5, performing solvent degreasing treatment on the cemented carbide rod blank in deionized water, the degreasing time is 5 hours, the degreasing temperature is 45°C, and vacuum drying is performed after degreasing;

[0063] S6, placing the degreased and dried cemented carbide rod blank into a sintering furnace for sintering, cooling it after taking it out of the furnace, and grinding and polishing it to obtain a cemented carbide rod;

[0064] During the sintering process, the cemented carbide rod blank was sintered using a four-stage sintering method;

[0065] S61, first stage: after evacuating the sintering furnace, supplying hydrogen, and heating the sintering furnace to 420°C at a rate of 30°C / min and then keeping the temperature for 4h;

[0066] S62, second stage: heating the sintering furnace to 1340°C at a rate of 50°C / min, supplying argon gas, and sintering for 50 minutes in an inert gas environment;

[0067] S63, the third stage: continue to supply argon gas to make the pressure in the sintering furnace reach 55mbar, and heat up to 1570℃, and keep warm for 30min;

[0068] S64, the fourth stage: After naturally cooling to 1050°C, keep warm for 20 minutes, and then cool to room temperature at a rate of 70°C / min.

[0069] Example 2

[0070] A method for processing a cemented carbide rod for a PCB milling cutter comprises the following steps:

[0071] S1. Prepare the raw materials according to the following weight percentages: WC powder: 92wt%, CoCrFeMnNi powder: 4wt%, Cr 3 C 2 Powder: 1.4wt%, cBN powder: 2.6wt%; wherein the particle size of the WC powder is 1μm, the particle size of the CoCrFeMnNi powder is 1.2μm, and the particle size of the Cr 3 C 2 The particle size of the powder is 0.4 μm, and the particle size of the cBN powder is 0.3 μm;

[0072] S2, putting the raw materials obtained in step S1 into a ball mill, with a ball-to-material ratio of 4:1, a ball milling speed of 600 r / min, and a ball milling time of 22 h, and then adding CNTs / Ni solvent for ball milling for 2 h to form a uniform ball milling slurry; wherein the ball milling body in the ball mill has a diameter of 4 mm and the ball milling body is a zirconia ball;

[0073] The weight percentage of the CNTs / Ni solvent in the mixed slurry is 1wt%; the preparation method of the CNTs / Ni solvent is: adding nickel sulfate, potassium sodium tartrate, sodium citrate, and anhydrous sodium carbonate to a mixed solution of deionized water and hydrazine hydrate, stirring evenly to obtain a chemical plating solution, then adding CNTs particles to the chemical plating solution, dripping sodium hydroxide to maintain the pH value at 8, stirring in a 75°C water bath for 1h, then centrifuging to neutrality, drying to obtain CNTs / Ni particles, and finally placing the CNTs / Ni particles in an ethanol solution for ultrasonic dispersion for 30min to obtain a CNTs / Ni solvent;

[0074] Among them, in the chemical plating solution, the weight ratio of deionized water and hydrazine hydrate is 50:1, the content of nickel sulfate is 0.15 g / L, the content of potassium sodium tartrate is 0.09 g / L, the content of sodium citrate is 0.12 g / L, and the content of anhydrous sodium carbonate is 0.12 g / L; the weight ratio of CNTs particles to chemical plating solution is 2:10; the weight ratio of CNTs / Ni particles to ethanol solution is 2:20.

[0075] S3, drying the ball-milled slurry obtained in step S2 in a vacuum drying oven, and obtaining WC-CoCrFeMnNi composite powder after sieving and granulating, wherein the particle size of the WC-CoCrFeMnNi composite powder is 0.8 μm;

[0076] S4, pouring the WC-CoCrFeMnNi composite powder into a cylindrical graphite mold, and molding the WC-CoCrFeMnNi composite powder by a hydraulic press to obtain a cemented carbide rod blank; wherein the pressure of the hydraulic press on the cylindrical graphite mold is 150 MPa, and the molding time is 8 minutes;

[0077] S5, performing solvent degreasing treatment on the cemented carbide rod blank in deionized water, the degreasing time is 5 hours, the degreasing temperature is 65°C, and vacuum drying is performed after degreasing;

[0078] S6, placing the degreased and dried cemented carbide rod blank into a sintering furnace for sintering, cooling it after taking it out of the furnace, and grinding and polishing it to obtain a cemented carbide rod;

[0079] During the sintering process, the cemented carbide rod blank was sintered using a four-stage sintering method;

[0080] S61, first stage: after evacuating the sintering furnace, hydrogen is supplied, and the sintering furnace is heated to 630°C at a rate of 45°C / min and then kept at this temperature for 4h;

[0081] S62, second stage: the sintering furnace is heated to 1460°C at a rate of 65°C / min, argon gas is supplied, and sintering is performed in an inert gas environment for 75 minutes;

[0082] S63, the third stage: continue to supply argon gas to make the pressure in the sintering furnace reach 75mbar, and heat up to 1590℃, and keep warm for 45min;

[0083] S64, the fourth stage: After naturally cooling to 950°C, keep warm for 20 minutes, and then cool to room temperature at a rate of 55°C / min.

[0084] Comparative Example 1

[0085] The processing method of the cemented carbide rod for PCB milling cutter of this comparative example 1 is different from that of the embodiment 1 in that: in step S1, Cr is not added. 3 C 2 powder.

[0086] Comparative Example 2

[0087] The processing method of cemented carbide rod for PCB milling cutter of this comparative example 2 is different from that of example 1 in that in step S1, cBN powder is not added.

[0088] Comparative Example 3

[0089] The processing method of cemented carbide rod for PCB milling cutter of this comparative example 3 is different from that of example 1 in that in step S2, no CNTs / Ni solvent is added during the ball milling process.

[0090] Comparative Example 4

[0091] The processing method of cemented carbide rod for PCB milling cutter of comparative example 4 is different from that of embodiment 1 in that: in step S2, the weight percentage of CNTs / Ni solvent in the mixed slurry is 7wt%.

[0092] Comparative Example 5

[0093] The processing method of cemented carbide rod for PCB milling cutter of this comparative example 5 is different from that of embodiment 1 in that: in step S2, the weight ratio of CNTs particles to chemical plating solution is 4:10.

[0094] Comparative Example 6

[0095] The processing method of cemented carbide rod for PCB milling cutter of this comparative example 6 is different from that of embodiment 1 in that the sintering temperature in step S63 is 1480°C.

[0096] Comparative Example 7

[0097] The processing method of cemented carbide rod for PCB milling cutter of comparative example 7 is different from that of embodiment 1 in that: in step S64, natural cooling is adopted to reduce the temperature to room temperature.

[0098] The following experiments are conducted on the above-mentioned embodiments 1-2 and comparative examples 1-7 to verify or understand their performance. In the cemented carbide rods prepared in the above-mentioned embodiments 1-2 and comparative examples 1-7.

[0099]

[0100]

[0101] Table 1 Comparison of cemented carbide rod performance tests of various embodiments and comparative examples

[0102] According to Table 1 above, the cemented carbide bars prepared in Example 1 and Example 2 use Cr 3 C2 The powder and cBN powder dual grain inhibitor can make the cemented carbide rod obtain higher wear resistance, excellent thermal stability and corrosion resistance, thereby improving the overall mechanical properties and service life; CNTs in CNTs / Ni solvent can form a high thermal conductivity channel during the sintering process, thereby improving the heat distribution and making the sintered body denser. At the same time, CNTs can connect the WC interface, reduce thermal resistance, and increase the thermal diffusion coefficient of the cemented carbide rod; Ni particles on the surface of CNTs / Ni can be magnetized to increase the coercive force of the cemented carbide rod, thereby enhancing resistance to external magnetic fields, so that the PCB milling cutter has better impact resistance during high-load and high-speed cutting; during the sintering process In the process, a four-stage sintering method is adopted. In the first stage, the oxides are reduced by hydrogen to ensure the purity of the material and improve the density and strength of the material. The rapid heating and inert gas protection in the second stage can effectively prevent excessive grain growth and oxidation, ensure the densification and uniformity of the material, and improve the mechanical properties. The high temperature insulation in the third stage can promote the full development of the FCC phase, make the grain structure uniform and stable, and enhance the toughness and plasticity of the material. The cooling in the fourth stage controls the transformation of the FCC phase to the BCC phase, forming a reasonable ratio of the FCC phase and the BCC phase, so that the material has both high toughness and high strength, adapts to high stress and high wear environment, and improves the crack resistance.

[0103] In Comparative Example 1, Cr 3 C 2 Powder can inhibit the growth of WC grains during sintering. If Cr is not added 3 C 2 Powder makes WC grains grow easily during high-temperature sintering, resulting in the microstructure of cemented carbide no longer being fine and uniform. This coarse grain structure will reduce the hardness and toughness of the material, thereby weakening its cutting performance and wear resistance;

[0104] In Comparative Example 2, cBN powder has extremely high hardness and wear resistance. If cBN powder is not added, the overall hardness of the cemented carbide material will be reduced and its wear resistance will also be weakened. This will shorten the service life of the tool in high-wear applications of PCB milling cutters and make it more susceptible to wear or passivation during the cutting process;

[0105] In Comparative Example 3, CNTs can form a high thermal conductivity channel during the sintering process, improve heat distribution, and make the sintered body more dense. If the CNTs / Ni solvent is not added, the thermal conductivity of the material will be reduced, resulting in uneven heat distribution during the sintering process, affecting the densification effect of the material; and the Ni particles in the CNTs / Ni solvent can be magnetized, thereby increasing the coercive force of the cemented carbide rod and enhancing its resistance to external magnetic fields; if the solvent is not added, the anti-magnetic interference ability of the cemented carbide rod will be weakened, thereby reducing the impact resistance of the cemented carbide rod during high-load and high-speed cutting;

[0106] In Comparative Example 4, CNTs have strong van der Waals forces and are easy to agglomerate. When the ratio of CNTs / Ni solvent is too high, the attraction between particles increases, causing CNTs particles to agglomerate in the slurry to form large agglomerates. These agglomerates are difficult to distribute evenly during the sintering process, resulting in uneven microstructure of the material, and even cracks or defects, which in turn affect its mechanical properties.

[0107] In Comparative Example 5, too high a CNTs content results in insufficient nickel ions in the chemical plating solution, thereby failing to evenly cover the surfaces of all CNTs particles. This results in incomplete nickel plating on the surfaces of some CNTs, forming an uneven coating, thereby affecting the thermal conductivity and mechanical properties of the material.

[0108] In Comparative Example 6, a higher sintering temperature is conducive to atomic diffusion and rearrangement between particles, thereby promoting material densification. If the sintering temperature is only 1480°C, insufficient atomic diffusion will result, and the ideal densification effect cannot be achieved. More pores may remain inside the material, thereby reducing the density and strength of the cemented carbide, and some FCC phases cannot be fully formed, affecting the toughness and impact resistance of the material.

[0109] In Comparative Example 7, the natural cooling rate is slow, resulting in that part of the FCC phase in the material is not fully converted into the BCC phase. Since the BCC phase has higher strength and hardness, and the FCC phase has better toughness and plasticity, failure to fully convert the phases will result in insufficient BCC phase content in the material, thereby reducing the overall strength and hardness of the material.

[0110] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for processing cemented carbide rods for PCB milling cutters, characterized in that: The following steps are involved: S1. Prepare the raw materials according to the following weight percentages: WC powder: 80-92wt%, CoCrFeMnNi powder: 4-12wt%, Cr3C2 powder: 0.5-1.4wt%, cBN powder: 2-8wt%; S2, putting the raw materials obtained in step S1 into a ball mill, with a ball-to-material ratio of 3-4:1, a ball milling speed of 400-600 r / min, and a ball milling time of 22-36 h, and then adding CNTs / Ni solvent for ball milling for 2-4 h to form a uniform ball milling slurry; Wherein, the weight percentage of the CNTs / Ni solvent in the mixed slurry is 1-4wt%; S3, drying the ball-milled slurry obtained in step S2 in a vacuum drying oven, and obtaining WC-CoCrFeMnNi composite powder after sieving and granulating; S4, pouring the WC-CoCrFeMnNi composite powder into a cylindrical graphite mold, and compression molding the WC-CoCrFeMnNi composite powder by a hydraulic press to obtain a cemented carbide rod blank; S5, performing solvent degreasing treatment on the cemented carbide rod blank in deionized water, the degreasing time is 5-7h, the degreasing temperature is 45-65°C, and vacuum drying is performed after degreasing; S6. Put the degreased and dried cemented carbide rod blank into a sintering furnace for sintering, cool it down after taking it out of the furnace, and grind and polish it to obtain a cemented carbide rod.

2. The method for processing cemented carbide rods for PCB milling cutters according to claim 1, characterized in that: The preparation method of the CNTs / Ni solvent is: Nickel sulfate, potassium sodium tartrate, sodium citrate and anhydrous sodium carbonate are added to a mixed solution of deionized water and hydrazine hydrate, and stirred evenly to obtain a chemical plating solution. Subsequently, CNTs particles are added to the chemical plating solution, and sodium hydroxide is added dropwise to maintain the pH value at 8-9. After stirring in a 65-75°C water bath for 1-2 hours, the solution is centrifuged to neutrality and dried to obtain CNTs / Ni particles. Finally, the CNTs / Ni particles are placed in an ethanol solution for ultrasonic dispersion for 20-30 minutes to obtain a CNTs / Ni solvent.

3. The method for processing cemented carbide rods for PCB milling cutters according to claim 2, characterized in that: In the chemical plating solution, the weight ratio of deionized water to hydrazine hydrate is 50:1, the content of nickel sulfate is 0.13-0.15 g / L, the content of potassium sodium tartrate is 0.07-0.09 g / L, the content of sodium citrate is 0.1-0.12 g / L, and the content of anhydrous sodium carbonate is 0.1-0.12 g / L.

4. The method for processing cemented carbide rods for PCB milling cutters according to claim 3, characterized in that: The weight ratio of CNTs particles to chemical plating solution is 2:

10.

5. The method for processing cemented carbide rods for PCB milling cutters according to claim 4, characterized in that: The weight ratio of CNTs / Ni particles to ethanol solution was 2:

20.

6. The method for processing cemented carbide rods for PCB milling cutters according to claim 1, characterized in that: In step S2, the diameter of the ball mill in the ball mill is 4-12 mm, and the ball mill is a zirconia ball.

7. The method for processing a cemented carbide rod for a PCB milling cutter according to claim 6, characterized in that: In step S1, the particle size of the WC powder is 0.4-1 μm, the particle size of the CoCrFeMnNi powder is 0.6-1.2 μm, the particle size of the Cr3C2 powder is 0.2-0.4 μm, and the particle size of the cBN powder is 0.1-0.3 μm.

8. The method for processing cemented carbide rods for PCB milling cutters according to claim 7, characterized in that: In step S3, the particle size of the WC-CoCrFeMnNi composite powder is 0.2-0.8 μm.

9. The method for processing cemented carbide rods for PCB milling cutters according to claim 1, characterized in that: In step S4, the pressure of the hydraulic press on the cylindrical graphite mold is 150-240 MPa, and the molding time is 4-8 minutes.

10. The method for processing cemented carbide rods for PCB milling cutters according to claim 1, characterized in that: In step S6, the cemented carbide rod blank is sintered using a four-stage sintering method; S61, first stage: after evacuating the sintering furnace, supply hydrogen, and heat the sintering furnace to 420-630°C at a rate of 30-45°C / min and keep it warm for 4-6h; S62, second stage: heating the sintering furnace to 1340-1460°C at a rate of 50-65°C / min, supplying argon gas, and sintering in an inert gas environment for 50-75 minutes; S63, the third stage: continue to supply argon gas to make the pressure in the sintering furnace reach 55-75mbar, and raise the temperature to 1570-1590℃, and keep it warm for 30-45min; S64, the fourth stage: After naturally cooling to 950-1050°C, keep warm for 20-40 minutes, and then cool to room temperature at a rate of 55-70°C / min.